Management of Campus Community Radio in Makassar City [Pengelolaan Radio Komunitas Kampus di Kota Makassar ] - Emilsyah Nur (BBPSDMP KOMINFO MAKASSAR, 2013)
This study aims to determine the campus and community radio management problems faced ranging from: Strengthening Networks (frequency), advocacy (legal legitimacy and policy), Fundraising (availability of facilities and supporting facilities pre-Broadcasting), Financial (broadcasting operational availability of funds), International and Intergovernmental Relationsanary. The Members of Community Radio. The research was conducted in the city of Makassar from January to March 2013 by taking a sample of 3 (three) informants who represent the college radio radio in Makassar with a technique of qualitative descriptive case study. Observation methods were used in data collection and in-depth interviews with a proportional random sampling. The results showed that the management of the campus and community radio creativity in Makassar still have problems in the field of regulation of frequency allocation policy, a certain freedom in certain broadcasting, Human Resource Readiness, supporting infrastrktur and broadcasting facilities, and financial support for the campus radio operations.Penelitian ini bertujuan untuk mengetahui pengelolaan radio komunitas kampus dan permasalahan yang dihadapi mulai dari : Penguatan Jaringan (frekwensi), Advokasi (legitimasi hukum dan kebijakan), Fundraising (ketersediaan sarana dan pra-sarana pendukung Penyiaran), Financial (Ketersediaan dana operasional penyiaran), dan Hubungan Internasional Antar Negara Anggota Radio Komunitas. Penelitian ini dilaksanakan di kota Makassar dari bulan Januari sampai Maret 2013 dengan mengambil sampel sebanyak 3 (tiga) informan radio kampus yang mewakili keseluruhan radio kampus yang ada di Makassar dengan teknik deskritif kualitatif dengan menggunakan studi kasus. Metode pengumpulan datanya menggunakan observasi dan wawancara mendalam (indepth interview) dengan penarikan sampel acak proposional. Hasil penelitian menunjukkan bahwa pengelolaan serta kreatifitas radio komunitas kampus di kota Makassar masih mengalami hambatan dibidang regulasi kebijakan alokasi frekwensi, kebebasan dalam penyiaran tertentu, kesiapan SDM pengelola siaran radio kampus, infrastrktur pendukung sarana penyiaran, dan financial dukungan operasional radio kampus tersebut.